?STUDIES ON LVARI RIVER EFFLUENT (Biological Sciences - PJSIR, 1999)
The study was aimed at determining the physical (TS, TSS, TDS, TVS) and chemical (CI, S04' NH3,BOD5, COD, DO) characteristics aswell asheavy metals presentin theLyari rivereffluent so asto identify theextent ofpollution. The average results of each parameterof twelvedifferent sites werecompared with that of the National Environmen- tal Quality Standards (NEQS). BOD5 andCODlevelswerewellabovetheNEQSwhiletheNH3-Nconcentration was low. Concentrations of Cd andZn were withinthe range while that of Pb, Cr, Ni and Cu were higher than the NEQS attimes. This indicates thatheavy pollutionloadisenteringintotheArabianSeacreatingtremendousharmespecially to marine life.